Quality of Hemoglobin (Hb) Examination Services for Pregnant Women at the AMIRA Primary Clinic in the JKN Scheme - Herwandono, Tulus Agreena; Kalla, Nur Ajizah Kalla (STIKES Hesti Wira Sriwijaya, 2026)
Executive Summary Hemoglobin (Hb) testing is an essential part of antenatal care (ANC) services to detect anemia in pregnant women. AMIRA Primary Clinic provides Hb testing as a routine service without additional fees under the National Health Insurance (JKN) scheme. The results show that Hb testing provides significant clinical and economic benefits, but faces obstacles in adherence to Fe tablet consumption, limited counseling time, and administrative burdens.